2004
DOI: 10.1128/aem.70.7.4216-4221.2004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Discrimination between 15 Fish Pathogens by Using 16S Ribosomal DNA PCR and DNA Microarrays

Abstract: We developed a DNA microarray suitable for simultaneous detection and discrimination between multiple bacterial species based on 16S ribosomal DNA (rDNA) polymorphisms using glass slides. Microarray probes (22-to 31-mer oligonucleotides) were spotted onto Teflon-masked, epoxy-silane-derivatized glass slides using a robotic arrayer. PCR products (ca. 199 bp) were generated using biotinylated, universal primer sequences, and these products were hybridized overnight (55°C) to the microarray. Targets that annealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 23 publications
1
71
0
Order By: Relevance
“…All Flavobacterium psychrophilum stains used in this study are described in Table 1 (Warsen et al 2004) and 8 of the strains were also confirmed by a nested PCR assay (Baliarda et al 2002) as part of a separate study (K. Cain & D. Call unpubl. data).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All Flavobacterium psychrophilum stains used in this study are described in Table 1 (Warsen et al 2004) and 8 of the strains were also confirmed by a nested PCR assay (Baliarda et al 2002) as part of a separate study (K. Cain & D. Call unpubl. data).…”
Section: Methodsmentioning
confidence: 99%
“…A microarray composed of rDNA oligonucleotides from 15 fish pathogens (Warsen et al 2004) was modified by the addition of a new oligonucleotide probe specific to a 16S rRNA gene polymorphism identified in Flavobacterium psychrophilum strain CSF 259-93 ( Fig. 1; GAAACACTCG-GTCGTGACCGAGCT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method enabled the identification of Vibrio and Photobacterium at the species level within a day including the PCR amplification step. Warsen et al (2004) developed a DNA array based on 16S ribosomal RNA gene for the discrimination of fish pathogens. By this method, 15 fish pathogens were simultaneously detectable, but only V. salmonicida was included in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their usefulness, DNA arrays have been utilized for bacterial identification (Call, 2005). Warsen et al (2004) developed a DNA array based on 16S ribosomal RNA gene for the discrimination of fish pathogens. Gonzalez et al (2004) reported the detection of marine fish pathogenic bacteria using multiplex PCR and DNA microarray.…”
mentioning
confidence: 99%